Pengaruh permainan Uno Card berbasis Matematika terhadap kemampuan mengenal lambang bilangan 1-10 pada anak tunagrahita ringan kelas III SLB Bangun Putra Kasihan - Syafitri, Zanatika (Literal: Disability Studies Journal, 2023)
The math-based uno card game can be used in recognizing number symbols, because it is a fun activity and the material being taught is conveyed. Researchers are trying to use this math-based uno card game to improve their ability to recognize number symbols. This study aims to find out the math-based uno card game in the ability to recognize number symbols in class III mild mentally retarded children at Bangun Putra Kasihan SLB. The approach used in this study is quantitative, with experimental methods. The design used in this study is the pre-test-post test experimental design. Data collection techniques used tests and documentation, then the data were analyzed using the Wilcoxon test. The results showed that there was an effect of the math-based uno card game on the ability to recognize number symbols 1-10 in children with mild mental retardation. Based on this research, it can be concluded that the math-based uno card game is effective in increasing the ability to recognize number symbols 1-10.